Konflik Antara Hukum Adat dan Hukum Nasional: Kasus Kawin Tangkap di Sumba - Djaga Mesa, Grendhard; Putra Frans, Mardian (LPPM Universitas Ekasakti Padang, 2024)
This study aims to investigate the conflict between customary and national laws in Sumba Barat Daya, particularly concerning the controversial practice of